The Influence of Potential Tourism Economic Zones on Community Welfare in the Soziona Tourism Economic Zone, Nias District, North Sumatra Province - Yarman Gulo; Sirojuzilam; Badaruddin; Agus Purwoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate the potential impact of the tourism economic area on the welfare of the people in the Soziona Tourism Economic Zone, Nias Regency, North Sumatra Province. The research method used is quantitative analysis. Data was collected through surveys and interviews with local residents, as well as analysis of secondary data related to tourism potential and welfare indicators. The results of the study indicated a positive relationship between the potential of the Soziona tourism economic area and community welfare. Tourism potential, which includes nature, culture, and supporting infrastructure, has a significant contribution to income and employment opportunities for the local community. This positive impact is also reflected in increased access to education, health care, and other public facilities.